Reflection on Teacher Organizational Citizenship Behavior: Antecedents of Perceived Organizational Support, Organizational Commitment and Job Satisfaction - Lie, Darwin; Agustina, Titien; Susanti, Desi; Basriani, Agustin; Sudirman, Acai (LPPM Undiksha, 2022)
Organizational citizenship behavior has recently received much attention among researchers, given its practical importance and implications for organizations. The importance of organizational citizenship behavior in teachers is because to achieve the school's vision and mission, organizational citizenship behavior is needed to make it happen. The primary purpose of this study was to analyze the contribution of perceived organizational support, organizational commitment and job satisfaction to organizational citizenship behavior. This research used a quantitative approach-oriented research design. For the acquisition of research data using documentation instruments and online questionnaire distribution. The sample used in the study were 110 respondents. The basis for determining the sample is oriented to the non-probability sampling approach by using the purposive sampling formula. This study concludes that perceived organizational support and job satisfaction have a significant effect on organizational citizenship behavior. Furthermore, the results of this study also confirm that organizational commitment has no significant effect on organizational citizenship behavior. In addition, perceived organizational support is the strongest predictor of influence on organizational citizenship behavior based on the results of the regression test and the most significant based on the results of the partial test.